Relationship of grade level and gender towards science literacy abilities in islamic senior high students - Husamah, H.; Syah, Wildan Akbar Alfiriyan; Chamisijatin, Lise; Luzyawati, Lesy (Jurnal Mangifera Edu, 2024)
Science literacy is one of the abilities that every individual student must have and is also a prerequisite for 21st-century life skills through integrated education, starting from family, school, and to society. This research aims to determine science literacy abilities and to determine the relationship between gender and class-level science literacy abilities in students in grades X, XI, and XII at Islamic Senior High School (ISHS) of Batu City. The research design used is quantitative research using descriptive methods (quantitative descriptive). The location of this research is at ISHS of Batu City. Purposive sampling was in the sampling process, which involved selecting a sample based on specific attributes, such as gender. There are 20 male and female students at the class level, and the results of ability in science literacy are X=46% and XI=60%. Based on this data, if it is based on the criteria for classes X, the results obtained for the gender aspect show that there is no significant interaction with the results of students' science literacy abilities. It can be concluded that there is a significant interaction between students’ science literacy skill and grade level.